Analisis Peningkatan Kinerja Simpang Tak Bersinyal (Studi Kasus : Jalan Dr. Wahidin – Jalan Pramuka – Jalan Lorong Bakso Di Kota Palu) - Nurfadillah Efendi, Muflihatun; Maylton Bose, Dregian; Ismadarni (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The Dr. Wahidin intersection – Jalan Pramuka – Jl Bakso is one of several intersections in the city of Palu. The traffic on this road is quite busy and sometimes there are queues of vehicles due to vehicle encounters, which results in congestion, reducing the comfort level. This study aims to determine the performance of the Jl. Dr. Wahidin – Jl. Scouts – Jl. Meatballs in serving traffic flow in the present and in the future and knowing solutions in solving problems at unsignalized intersections Jl.Dr, Wahidin - Jl. Scouts – Jl. Meatball. Data collection was obtained based on primary and secondary data, primary data namely traffic volume, geometric intersections, and side barriers, secondary data in the form of maps of the city of Palu, population, and number of vehicle growth. From the results of research and discussion at the Dr Wahidin intersection - Jalan Pramuka - Jl Bakso, the total volume of traffic flow (Qtot) is 2337 pcu/hour, Capacity (C) is 4655.1 pcu/hour, Degree of Saturation (DS) is 0, 51, and queue odds (QP) 11-25%. Based on the results of the study, the performance of the Dr. Wahidin - Jalan Pramuka - Jl Bakso intersection has a stable flow level of service (C), but controlled vehicle speed and motion.